Reply to Ortner - Josef Schosser (Games, 2018)
I address the comments made by Ortner (Games 9(4): 93, 2018) in relation to my note 'Incentive Systems for Risky Investment Decisions Under Unknown Preferences: Ortner et al. Revisited' (Games 9(2): 26, 2018).
Keywords: D82; G31; M46; 330; investment decision; performance measure; relative benefit cost allocation